Harmonic Convergence? Constitutional Criminal Procedure in an International Context - Amann, Diane Marie (2000)
Throughout the world, a trend toward a shared - a constitutional - criminal procedure may be detected. It is evident in common-law, civil-law, and mixed systems: individual states like China adopt laws promising once-alien concepts like a presumption of innocence, even as supranational bodies like the International Tribunal for the former Yugoslavia debate how to adapt certain norms to a hybrid structure. Some have suggested that such developments may herald a harmonic convergence of criminal procedure rules. This Article examines the likelihood of such a convergence. It establishes as a keynote around which harmony may develop the model of constitutional criminal procedure. Constructed in the United States in the first part of the twentieth century, the model embodies the belief that the state must treat accused individuals equally, with due respect for their liberty; that is, with fundamental fairness. The Article then traces movements toward convergence: changes after the French Revolution; the Nuernberg trials and the rise of the individual in international law; increased law-enforcement cooperation to fight global crime; ongoing European integration; and the development of ad hoc international criminal tribunals and proposals for a permanent international criminal court. It then sounds notes of discord, with attention to China and the Islamic states, and France and the United States. The Article demonstrates that movement toward convergence will continue. States that share a fundamental rights tradition and a desire for economic and political integration may approach harmony. But some states will resist pressures to conform - even if the international norm corresponds with their own cultural tradition - out of perceived threats to their security or position within the world community